Pemberian antibiotik cefotaxime dengan konsentrasi sublethal pada isolat Klebsiella pnuemoniae yang resisten terhadap ampicilin menginduksi Multi Drug Resisten (MDR) - Gema Zakharian; Dewa Made Sukrama; Ni Nengah Dwi Fatmawati (DiscoverSys Inc., 2018)
Background: Antibiotic resistance causes frequent infections to be difficult to treat and may aggravate the condition of infected patients which are requiring longer and more expensive antibiotic therapy. Klebsiella sp. is the most potential germ that causes nosocomial infections in the hospital. Klebsiella sp. which resulted a positive ESBL being perceived to directly exacerbate public health problems and become the center of attention in some countries, including Europe and America. Methods: This study used 32 repetitions with Klebsiella pneumoniae isolate obtained from Clinical Microbiology Installation of Sanglah General Hospital. Isolate was divided into two groups, the first group was not given the treatment of cefotaxime with sublethal concentration and the second group was given the treatment of cefotaxime with sublethal concentration. Resutls: The results of the treatment were tested by Pearson Chi Square method with the result that cefotaxime treatment with sublethal concentration significantly caused resistance to Klebsiella pneumoniae isolate and was proved by p value of 0.014 (p <0.05). Conclusions: Antibiotic test results using Vitex found isolates Klebsiella pneumoniae are resistant to more than two antibiotics and isolates are also germs that have Extended Spectrum Beta-Lactamase (ESBL).